Numerical analysis for transient processes of hydropower and water-supply systems sharing a headrace tunnel. Issue 5 (March 2019) - Yang, J B; Yang, J D; Guo, W C; Ma, A T
Abstract: In order to achieve both hydropower generation and water supply, some hydropower stations with high enough water quality are able to provide water to downstream areas by drawing water directly from the headrace tunnel. Hydraulic interference can occur during these transient processes because the headrace tunnel is partially shared by both the hydropower and water-supply system. This paper uses numerical methods to examine the transient processes of the hydropower and water-supply systems sharing a headrace tunnel, using the Nanshui Reservoir Project as a case study. First, a mathematical model for the hydropower and water-supply system of the selected project is developed. Next, the influence of the closing and opening modes of the guide vanes and the water-supply system valves on the water conveyance system, the surge-chamber surge water levels and unit parameters is analyzed for the normal operating conditions of the hydropower and water-supply system. Results show that the water hammer wave generates by the closing and opening of the valve or the guide vane propagates upstream along the pipelines of its own, and then transmits into the opposite conduits at the intake point, ultimately inducing pressure fluctuations in the conduits and unit output swings. Nonetheless, the negative impacts can be minor. On the other hand, because of the transmission (as opposed to total reflection) of the water hammer wave at the intake point, a pressure relief role is exerted here to some extent.